PEMETAAN KARYA TAFSIR DI ARAB SAUDI - Fitria, Riri (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2011)
This paper will not discuss about the development of the county in economic, political and other, but specialize discussion n interpretation development and their interpreter. As for the interpreter to be targeted, for a more comprehensive description, the author here does not follow the rules of previous papers, this is only by focusing to the original Arabian?s interpreter, but also in al-mufassirûn al-wâfidûn, which in not a Arabian, but they wrote an interpretation on the state. At the end of the paper, the author conclude tat work of interpretation in the country of Saudi of Arabia in general using the al-tahlîlî with fiqhî style and i?tiqadî. In term of methodology, in the county of Saudi Arabia patterned in wahabism an it is no so let the flexibility ration other than in accordance with what has been laid down by generation of salaf al-sâlih so that the interpretation in Saudi Arabia tend let behind than Egypt which more let the use of ratios.